PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KIMIA PESERTA DIDIK KELAS XIIPA-1 SMA N 1 CIWARINGIN PADA MATERI LAJU REAKSI - Yusuf Satori (Jurnal Redox, 2019)
The formulation of the problem in this study is,do the Problem Based Learning model improve teacher skills, activities, and student learning outcomes?. The purpose of this study was to improve skills, teachers, student activities, and learning outcomes of grade XI IPA-1 of students at Ciwaringin 1 High School in Chemistry learning through the Problem Based Learning model.The design of this study is classroom action research through the Problem Based Learning model using two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The research subjects were teachers and students of grade XI IPA-1 of Ciwaringin 1 High School. The technique of collecting data uses observation and tests.The results of the study show that: (1) the teacher's skills in the first cycle obtained a score of 22 with good criteria, Cycle II with a score of 27 with good criteria. (2) in the first cycle activity students got a score of 16 with good criteria, the second cycle obtained a score of 19 with good criteria. (3) Classical completeness of learning outcomes of students in the first cycle of meeting 1 was 19.44% and the first cycle of meeting II was 66.67%. In the second cycle of meeting I was 75.00% and the second cycle of meeting II was 91.67%.The conclusion of this study is that through the Problem Based Literacy model, it can improve teacher skills, student activities, and learning outcomes in Chemistry learning. Suggestions are that teachers can use the Problem Based Learning model to improve the quality of learning inother subjects and other classes. Keywords: Learning Model “Problem Based Learning” Activities and Learning Outcomes.